Oliver Twist - Dickens, Charles, 1812-1870 (Oxford : Oxford University Press, 1992)
Oliver Twist is a desperate orphan. A gang of thieves takes him in and teaches him to steal, but then he is caught. What will become of poor Oliver Twist? Kids can find out in this easy-to-read chapter book adaptation of the Dickens classic.
O
700
O
Keywords: Kidnapping victims -- Fiction; Criminals -- Fiction; Orphans -- Fiction; Bildungsromans